2015
DOI: 10.4000/etnografica.4020
|View full text |Cite
|
Sign up to set email alerts
|

The Pentecostal reworking of male identities in Brussels: producing moral masculinities

Abstract: vol. 19 (2) | 2015Inclui dossiê "Masculinities in times of uncertainty and change"The Pentecostal reworking of male identities in Brussels: producing moral masculinities The text is a facsimile of the print edition. Reconfigurações pentecostais de identidades masculinas em Bruxelas: a produção de masculinidades morais © CRIAThe Pentecostal reworking of male identities in Brussels: producing moral masculinities Maïté MaskensAddressing the paradoxes of gender in Pentecostal churches attended by converts of Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A study conducted in Zambia suggested that women’s attitudes and practices around gender norms might partly stem from interpretations of the biblical story of creation as evidence of women’s inferiority in relation to men in relationships [ 45 ]. Also, both women and men might hold the view that women are not equal to men [ 52 ]. To this end, certain church teachings revolve around women serving men’s sexual needs and subordinating their own sexual feelings to that of men even when they have little benefit.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Zambia suggested that women’s attitudes and practices around gender norms might partly stem from interpretations of the biblical story of creation as evidence of women’s inferiority in relation to men in relationships [ 45 ]. Also, both women and men might hold the view that women are not equal to men [ 52 ]. To this end, certain church teachings revolve around women serving men’s sexual needs and subordinating their own sexual feelings to that of men even when they have little benefit.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study has indicated that certain African churches could be contributing progressively to the transformation of harmful norms of masculinities [ 19 ]. Therefore, given the population coverage, churches in Africa may provide a compelling setting and a powerful socialisation platform for engaging large numbers of youth with positive attitudes and behaviours towards gender equality and with discourses such as those supporting positive forms of masculinities [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the Pentecostal work on masculinity also breaks with the dominant cultural model of masculinity, the local “hegemonic” masculinities. (2015, 332)The discourse within Pentecostalism strengthens “masculine” hegemony; however, Pentecostal beliefs and practices, rooted in Scripture, break the dominance of that cultural model . Demonstrating this attribute, Mario, a Guatemalan follower for more than 40 years, living in Belgium for about 12 years and attending the biggest Congolese Church in Brussels, said, after a long prayer during which tears were running down his face:
“Society says you cannot cry, you cannot be sensitive otherwise you are considered gay.
…”
Section: Discussionmentioning
confidence: 99%
“…]. You're also told that you have to fuck to be a man otherwise we say you're homosexual, but it is wrong too.” (Maskens 2015, 338)Socially constructed gender “norms” tell men that they cannot cry and women that they cannot lead; yet, through the Spirit, these hegemonic structures are transgressed, enabling fluidity and freedom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation